Interaction of periodontal clinical indicators in metabolic syndrome and nonalcoholic fatty liver disease: Implications for preventive interventions - Rocío Valenzuela-Narváez; Daniel Valenzuela-Narváez (Elsevier, 2024)
Introduction: The behavior of periodontal clinical indicators in metabolic syndrome (MetS) and fatty liver disease (NAFLD) are not clearly defined. It's even considered that high-risk cases for NAFLD are currently underreported or not identified in a timely manner. The aim of the study is to elucidate the interaction of periodontal clinical indicators in MetS and NAFLD. Materials and methods: 336 patients were eligible because they met the diagnostic criteria for metabolic syn-drome and nonalcoholic fatty liver disease. Those selected were randomly selected for a cross-sectional study. Metabolic status and non-alcoholic fatty liver disease were measured using the MetS Metabolic Syndrome Diagnostic Criteria (NCEP/ATP-III) and laboratory tests, respectively. In addition, periodontal clinical indicators were evaluated: probing depth, clinical attachment, plaque index and gingival bleeding. Results: The association for NAFLD and probing depth was p = 0.736. The association for MetS and probing depth was p = 0.598. For NAFLD and clinical attachment loss, the association was p = 0.751. For MetS and clinical attachment loss, the association was p = 0.435. The plaque index for MetS was p = 0.238. The plaque index for NAFLD was p = 0.269. The gingival bleeding association for NAFLD was p = 0.673 and for MetS was p = 0.522. Conclusions: Periodontal clinical indicators of metabolic syndrome were as-sociated with elevated serum levels of low-density lipoproteins (LDL), HDL-cholesterol, and triglycerides. However, when comparing the values in NAFLD and MetS, a greater significance is evident in the first study group.